Où en est l’édition de textes patristiques grecs aujourd’hui ? Théories, méthodes et pratiques - Cassin, Matthieu (Zeitschrift für antikes Christentum, 2020)
An overview of recent editions of Greek texts from Christian Antiquity is provided, with particular attention to the question of theories and methods of edition. First, we recall the main methods involved: the Lachmannian method, corrected or not by historical approaches, New Philology, etc. In a second step, we go through some large collections of editions of patristic texts, in order to identify their specificities and study their main recent productions; these are successively examined: Athanasius Werke; Gregorii Nysseni Opera; Die griechischen christlichen Schriftsteller der ersten Jahrhunderte; Patristische Texte und Studien; Corpus christianorum, series graeca; Sources chrétiennes. Some special cases are then considered: single-witness texts; treatment of overabundant traditions and phylogenetic methods; partial editions; anthologies, exegetical catenae and compilations. Finally, we propose a general reflection on the changes introduced in the editing process by the introduction of digital technologies, up to and including electronic edition itself.